Los circuitos políticos: cambios institucionales y nuevos movilizadores de la organización política estudiantil en el Perú - Chávez Angeles, Noelia (2016)
Peru does not have an articulated and organized student movement that promote clear agendas to improve the quality of higher education. Still, students compete in elections for seats at their university’s governing bodies. This is the case of the National University of Peruvian Amazon (UNAP), where student’s political groups have increased in recent years without a clear agenda about university development. This article explores this paradox describing the new mobilizers for students’ organizations.Firstly, the findings suggest that university’s governing bodies operate under a clientelistic logic between students and authorities. However, at the same time some students have built a new interest in local and regional politics as a result of the Peruvian decentralization process. Therefore, student organizations are also functioning as political operators and supporters of the regional movements.The “big politics” continue to intervene in “petty politics”, and vice versa, turning the university into a relevant arena and students into key actors to understand subnational politics and the functioning of “democracies without parties”.